The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1590/s0100-879x1997001000012
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase activity in the pons and medulla oblongata of rats after chronic electroconvulsive shock

Abstract: An imbalance between cholinergic and noradrenergic neurotransmission has been proposed for the etiology of affective disorders. According to this hypothesis, depression would be the result of enhanced cholinergic and reduced noradrenergic neurotransmission. Repeated electroconvulsive shock (ECS) is an effective treatment for depression; moreover, in laboratory animals it induces changes in brain noradrenergic neurotransmission similar to those obtained by chronic treatment with antidepressant drugs (down-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…With regard to the cholinergic system, previous studies examined postictal brains in rats and revealed a decrease in the number of muscarinic binding sites without compensatory increase in the affinity of the ligand for this receptor. Also, significant reductions in acetylcholine levels and an increased activity of the enzyme choline acetyltransferase directly after ECT were seen (Longoni et al ., ; Camarini and Benedito, ). These pathophysiological findings support the hypothesis that acetylcholine is involved in cognitive side effects induced by ECT.…”
Section: Introductionmentioning
confidence: 97%
“…With regard to the cholinergic system, previous studies examined postictal brains in rats and revealed a decrease in the number of muscarinic binding sites without compensatory increase in the affinity of the ligand for this receptor. Also, significant reductions in acetylcholine levels and an increased activity of the enzyme choline acetyltransferase directly after ECT were seen (Longoni et al ., ; Camarini and Benedito, ). These pathophysiological findings support the hypothesis that acetylcholine is involved in cognitive side effects induced by ECT.…”
Section: Introductionmentioning
confidence: 97%